Atividade de formação de professor de ciências: produção de resumos - Gonçalves, Leticia Reina (2011)
This dissertation aims to develop a collaborative-critical work with a teacher of Science in order to understand and to transform the work with production of written summaries of expository texts which were read by the students. Specifically, this research aims to understand critically the meanings brought by the participants and how they share new meanings on the summary of expository texts as a tool for teaching-learning in Science classes. The research is organized through two socialhistorical activities (Reflexive Session and Class) that are related, in part, by the object summary production and the participants researcher and teacher , that enable the learning concepts to be understood, questioned and shared, like a creative chain (Liberali, 2011) and that contextualize the critical formation for the research participants. It is supported by Social-Historical-Cultural Activity Theory (TASHC), which conceives the man's work activity as a way for transforming society and the man himself. It s also supported by Bakhtin/Volochinov s discussions about the ways the subject is constituted as a social being, inserted in a particular context of communication and implicated in oral and written productions, in these specific situations. The discussions through TASCH provide an understanding of contexts of teacher formation in which the language enables the construction of ZPDs (Zones of Proximal Development) for the participants understanding and sharing of meanings. The contributions given by Dolz & Schneuwly (2004) will assist in understanding language organization in social practices with the genre summary , as a tool of teaching-learning in reading and writing texts. The Collaborative Critical Research, as discussed by Magalhães (2007; 2009; 2010) e Magalhães & Oliveira (2011) supports the methodological choices in close relationship within the theoretical base and the research contents. The analyzed data were produced during Reflexive Sessions with a teacher of Natural Science and through observing some of her classes. The results show the complexity of the collaborative-critical work and the transformation in some concepts on written production of summaries as an instrument of teaching-learning Science